Intimate Partner Violence, Its Sociocultural Practice, and Its Associated Factors Among Women in Central Ethiopia - Tesfa A; Dida N; Girma T; Aboma M (Dove Medical Press, 2020)
Ayantu Tesfa, Nagasa Dida, Teka Girma, Mecha Aboma Department of Public Health, Medicine and Health Science College, Ambo University, Ambo, EthiopiaCorrespondence: Nagasa DidaDepartment of Public Health, Medicine and Health Science College, Ambo University, P.O. Box: 19, Ambo, EthiopiaTel +251913174508Email nadibefe@yahoo.comBackground: Intimate partner violence is a serious and widespread problem worldwide. It is a domestic violence by a spouse or partner in an intimate relationship against the other spouse or partner. Even though Ethiopia is also one of the countries where the condition has been seriously happening, there is a dearth of information in the study area.Objective: To assess the prevalence of intimate partner violence and its sociocultural practice, and its associated factors among married women in Oromia, Central Ethiopia.Methods: A community-based cross-sectional study was conducted on 671 women of Ambo district who were in marriage from March 1 to 30, 2018. Multistage sampling method was employed to select study participants. Data were collected using interviewer-administered WHO Multi-country Study on Women’s Health and Life Experiences Questionnaire. Descriptive, bivariate, and multivariate logistic regression analyses were done using SPSS version 20.0.Results: Out of 671 married women expected to participate, 657 of them participated in the study making a response rate of 98%. Overall, 77% (95% CI 73.7– 80.1%), and 62.4% (95% CI, 58.6– 66.1%) of the respondents reported that they have experienced intimate partner violence in their lifetime and in the last one year, respectively. Lack of formal education by husband (AOR 2.30, 95% CI 1.28– 4.15), housewife occupation of respondents (AOR 2.04, 95% CI 1.02– 4.06), number of children (AOR 4.37, 95% CI 1.40– 13.66), perceived husband dominance (AOR 1.74, 95% CI 1.15– 2.63), grow up in domestic violence (AOR 1.53, 95% CI 1.00– 2.35) and partner’s alcohol intake (AOR 1.77, 95% CI 1.12– 2.79) were independently associated with intimate partner violence.Conclusion: Intimate partner violence against women remains an important public health problem. This needs urgent attention at all levels of societal hierarchy including policymakers, stakeholders, and professionals to alleviate the situation.Keywords: intimate partner violence, women, prevalence, associated factors